Penyuluhan Kesehatan Penatalaksanaan Simpel Emergency Cedera Olah Raga Pada Warga Panti Asuhan An Nisa Kecamatan Jaten Karanganyar - Gatot Suparmanto; ika subekti wulandari (Pelita Masyarakat, 2023)
Simple Emergency Management (SEM) training is training on how to treat or handle people who get an accident or illness that suddenly comes before receiving help from medical personnel. can recognize how to treat patients with cases such as sports injuries that need serious treatment. The training this time was conducted for the students of the An Nisa Orphanage Jaten Karanganyar. There are 50 beneficiaries from the An Nisa Orphanage. The purpose of this counseling is to provide understanding to the residents of the orphanage regarding the first handling of emergency cases, especially in sports injuries so that the emergency situation does not spread to other things. -Things that are worse. The method used is the lecture and simulation method which is assisted by the emergency team from Kusuma Husada Surakarta, namely the Kusuma Nursing Car (KNC). After evaluating the residents, it was found that 90% of the residents understood how to take the first action in a case. Emergency.